Serum trace element levels and alopecia areata: Evidence on the need for specific interventions: Nivel sérico de oligoelementos y alopecia areata: Evidencia sobre la necesidad de intervenciones específicas - Duque-Mendoza, David Enrique (2025)
Alopecia areata is an autoimmune disease associated with zinc and vitamin D deficiencies. A recent meta-analysis found lower levels of these micronutrients in affected patients, suggesting a potential benefit from supplementation. However, higher-quality evidence is needed to confirm its effectiveness, especially given the possible systemic complications and the need for context-specific approaches.